Cross-Protective Efficacy of Influenza Virus M2e Containing Virus-Like Particles Is Superior to Hemagglutinin Vaccines and Variable Depending on the Genetic Backgrounds of Mice - Kim, Yu-Jin; Lee, Young-Tae; Kim, Min-Chul; Lee, Yu-Na; Kim, Ki-Hye; Ko, Eun-Ju; Song, Jae-Min; Kang, Sang-Moo (Frontiers in Immunology, 2017)
Influenza virus M2 extracellular domain (M2e) has been a target for developing cross protective vaccines. However, the efficacy and immune correlates of M2e vaccination are poorly understood in the different host genetic backgrounds in comparison with influenza vaccines. We previously reported the cross protective efficacy of virus-like particle (M2e5x VLP) vaccines containing heterologous tandem M2e repeats (M2e5x) derived from human, swine, and avian influenza viruses. In this study to gain better understanding of cross protective influenza vaccines, we compared immunogenicity and efficacy of M2e5x VLP, H5 hemagglutinin VLP (HA VLP), and inactivated H3N2 virus (H3N2i) in wild type strains of BALB/c and C57BL/6 mice, and CD4 and CD8 knockout (KO) mice. M2e5x VLP was superior to HA VLP in conferring cross protection whereas H3N2i inactivated virus vaccine provided high efficacy of homologous protection. After M2e5x VLP vaccination and challenge, BALB/c mice induced higher IgG responses, lower lung viral loads, and less body weight loss when compared to those in C57BL/6 mice. M2e5x VLP but not H3N2i immune mice after primary challenges developed strong immunity against a secondary heterosubtypic virus as a model of future pandemics. M2e5x VLP and HA VLP vaccines were able to raise IgG isotypes in CD4 KO mice. T cells were found to contribute to cross protection by playing a role in reducing lung viral loads. In conclusion, M2e5x VLP vaccination induced better cross protection than HA VLP, and its efficacy varied depending on the genetic backgrounds of mice, supporting the important roles of T cells.